A narrative review of the phenomenon of predatory journals to create awareness among researchers in veterinary medicine - Fadel, Charbel; Milanova, Aneliya; Suran, Jelena; Sitovs, Andrejs; Kim, Tae Won; Bello, Abubakar; Abay, Solomon Mequanente; Horst, Stefanie; Mileva, Rositsa; Amadori, Michela; Oster, Ena; Re, Giovanni; et al. (John Wiley and Sons, 2024)
In recent years, especially since the COVID-19 pandemic, the number of predatory journals has increased significantly. Predatory journals exploit the “open-access model” by engaging in deceptive practices such as charging high publication fees without providing the expected quality and performing insufficient or no peer review. Such behaviors undermine the integrity of scientific research and can result in researchers having trouble identifying reputable publication opportunities, particularly early-career researchers who struggle to understand and establish the correct criteria for publication in reputable journals. Publishing in journals that do not fully cover the criteria for scientific publication is also an ethical issue. This review aimed to describe the characteristics of predatory journals, differentiate between reliable and predatory journals, investigate the reasons that lead researchers to publish in predatory journals, evaluate the negative impact of predatory publications on the scientific community, and explore future perspectives. The authors also provide some considerations for researchers (particularly early-career researchers) when selecting journals for publication, explaining the role of metrics, databases, and artificial intelligence in manuscript preparation, with a specific focus on and relevance to publication in veterinary medicine.